ETMR-02. NOVEL CIC-LEUTX FUSION IN CNS EMBRYONAL TUMOR: A CASE REPORT AND REVIEW OF THE LITERATURE. (4th December 2020) - Hu, Wanming; Wang, Juan; Zhang, Xing; Ji, Yuhang; Song, Chao; Sun, Xiaofei
Abstract: INTRODUCTION: Central nervous system (CNS) embryonal tumor is a group of rare, poorly differentiated neuroepithelial malignant neoplasm predominantly occurs in pediatrics. Herein, we firstly report a CNS embryonal tumor harboring pathogenic CIC-LEUTX fusion. METHODS: Immunohistochemistry (IHC), Fluorescence in Situ Hybridization (FISH) and Next Generation sequencing (NGS). RESULTS: A 2-year-old male was found to have solid and cystic mass in left temporal lobe-basal ganglia and left parietal lobe (maximum diameter=75mm). The pathological diagnosis was CNS embryonal tumor (NEC) after totally resection. The tumor was poorly differentiated embryonal neoplasms of neuroectodermal origin that lacked the specific features and rosettes. IHC showed Syn was strongly/diffusely positive and Ki67 proliferation index was high (50%+), and copy number at the 19q13.42 C19MC locus showed no alterations. NGS showed pathogenic mutations including a brand new CIC-LEUTX fusion, heterozygous germline NBN c.C127T mutation and somatic TSC2 c.G2714A mutation. One month after operation, intracranial tumor recurred (maximum diameter=55mm) and spinal cord implantation metastasis occurred, and then the patient received chemotherapy (CTX+CBP+VCR/DDP+VP-16) and had significant improvement in symptoms and tumor shrinkage (maximum diameter=31mm). Literature review revealed CIC fusion predominantly presented in sarcomas, such as CIC-NUTM1 fusion in rare CNS sarcoma, CIC-LEUTX fusion in epithelioid angiosarcoma and CIC-DUX4 fusion in Ewing-like sarcoma. Hitherto, apart from this case, there were only two cases which had CIC-LEUTX fusion in CNS, including a case of CNS angiosarcoma and a case of anaplastic ganglioglioma. CONCLUSIONS: We firstly found a specific new type in CNS embryonal tumor with distinct molecular-pathological characteristics of CIC-LEUTX fusion.